Influence of environmental variability on meningitis in West African countries: pre- and post-vaccination - Diouf, Diarra; Martín-Rey, Marta; Rodríguez-Fonseca, Belén; Diouf, Ibrahima; Dione, Cheikh; Akinbobola, Ademola; Gaye, Amadou T. (Frontiers in Environmental Health, 2025)
IntroductionBacterial meningitis outbreak's, associated with high mortality, remain a significant public health challenge in West Africa. The environmental factors and mechanisms that trigger these outbreaks are not yet fully understood.MethodsThis study investigates the seasonal and inter-annual variability of meningitis incidence and its association with environmental variables. The analysis considers two distinct periods, 2006–2009 and 2010–2020, based on the MenAfriVac introduction's in 2010, across two climatic zones: the Sahelian (SAH) and Gulf of Guinea (GG) countries.ResultsThe results reveal that changes in the timing and magnitude of meningitis outbreaks between 2006 and 2009 and 2010–2020 are linked to variations in dust distribution, temperature trends, and their impact on relative humidity (RH). High concentrations of particulate matter (PM10) and increased aerosol optical depth (AOD) in January were identified as key precursors of meningitis outbreaks in both regions. In the SAH, meningitis outbreaks and their severity are strongly associated with increased dust levels and temperatures combined with RH below 20%. In contrast, in the GG, outbreaks are driven by high PM10 levels, temperature anomalies, and RH below 45%.DiscussionThe study shows that rising RH and shifts in wind patterns signal the end of the meningitis season. Additionally, vaccination programs slow bacterial interactions with antibodies, delaying disease transmission and prolonging the outbreak period. Despite the availability of vaccines, climate factors remain critical drivers of meningitis outbreaks. Given the ongoing challenges posed by climate change, enhanced surveillance systems and strategic public health interventions are essential for mitigating the impact of future outbreaks.